Oligosarcus itau - Alonso, Felipe (2022)
Dientudo Oligosarcus itau has most recently been assessed for The IUCN Red List of Threatened Species in 2020. Oligosarcus itau is listed as Endangered under criteria B1ab(iii)+2ab(iii).